Study of Characteristics of The Maize Corn Varieties Introduction and Some Local - Wika Winani Syahputri; Hot Setiado; Khairunnisa Lubis (Jurnal Agroekoteknologi, 2018)
WIKA W SYAHPUTRI:Characteristics Study Of The Introduction And Some Local Corn Varieties. Supervised by HOT SETIADO and KHAIRUNNISA LUBIS.The difference in the character of corn plants at different age, would perform different growth, besides the genetic factors also influenced by thecultivation. The high genetic diversity was one of the important factors to produce the new superior varieties.The research was aimed to know the characteristics of vegetative and generative of introduction and some local corn varieties. The research was carried out on the land of the Centre Seed Service of Cash Crops, Departmentof Agriculture,Medan Sunggal, Deli Serdang district, from July 2016 to  October 2016. The randomized block design was used with three varieties of corn (Black Aztec, Bisi2, Bonanza).The data obtained were analyzed and continued with the DMRT. Variables observed were: the plant height, the time of flowering, the time of female flowers bloomed, the time of harvested, the cob length, the number of lines per cob, the production per sample, the production per plot. The results showed that thevarieties significantly affected the plant height, the time of male flower bloomed, the time of harveste, the cob length, the number of line per cob, the production per sample, the production per plot. The Black Aztec showed the lowest production (1005.56 grams per plot) mean while the Bonanza showed the highest production (2338.44 grams). The highest heritability and the broad of diversity coefficient  were obtained in the time of male flower bloomed, the time of female flower bloomed, the time of harvested, the number of lines per cob.Key words: introduction, maize, varieties